Left Ventricular Twist and Circumferential Strain in Dogs with Myxomatous Mitral Valve Disease. (3rd June 2013) - Zois, N.E.; Olsen, N.T.; Moesgaard, S.G.; Rasmussen, C.E.; Falk, T.; Häggström, J.; Pedersen, H.D.; Møller, J.E.; Olsen, L.H.
<x xml:space="preserve">Abstract</x> Background During the cardiac cycle, the ventricle undergoes a twisting motion because of the oblique orientation of the left ventricular (LV) myofibers. This can be quantified by speckle‐tracking echocardiography (STE). In mitral regurgitation (MR) in humans, the short axis deformation has been suggested as being pivotal to LV function. Decreased and delayed LV twist has been described in experimental MR, but has not been studied in myxomatous mitral valve disease (MMVD). Hypotheses (1) Magnitude (CSt) and rate (CSRs) of systolic circumferential deformation decrease before the onset of congestive heart failure (CHF); (2) magnitude and rate of LV twist decrease, and onset of untwist is delayed, with increasing MMVD severity. Animals A total of 97 privately owned small‐ to medium‐sized dogs. Methods Severity of MMVD was assessed by echocardiography and presence of clinical signs of CHF. Magnitude and rate of LV twist and circumferential deformation were evaluated by STE. Results Dogs with CHF receiving treatment had increased CSt, CSRs, early diastolic untwisting rate, and delayed onset of untwist compared to dogs with minimal MMVD and increased systolic twist compared to dogs with mild MMVD (all P < .01). CSt and time to onset of untwist increased with echocardiographic variables of MR severity (all P < .002). CSRs and several LV twist variables decreased with increasing systolic LV internal diameter (all P < .01). Conclusions and Clinical Importance No STE‐derived variable was decreased before onset of CHF. In dogs with CHF receiving treatment, the delayed onset of relaxation might indicate LV dysfunction and the hyperdynamic CSt and LV twist reflect compensatory mechanisms.